(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
One of the most crucial aspects of non-stress testing is the mother’s health. Correct maternalposture reduces the potential for test-related mistakes and false positives and hence should be includedinto practice recommendations. The method was quantitative, taking the form of an experiment. Onehundred women in the semi-position fowler’s group and one hundred women in the supine group wererandomly chosen from the pool of pregnant women who were in the convenience sample. A non-stresstesting was performed to measure the foetal biophysiological parameters at baseline, and the mother’slevel of comfort was measured using a Verbal Numeric Rating Scale. The findings show that foetalparameters change somewhat between the two orientations. The degree of comfort in the semi-posturefowler’s is significantly correlated with that in the supine position (p< 0.05).